2003
DOI: 10.1097/00000374-200301000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine D2 Receptor Binding, Drd2 Expression and the Number of Dopamine Neurons in the BXD Recombinant Inbred Series: Genetic Relationships to Alcohol and Other Drug Associated Phenotypes

Abstract: The range of difference in receptor binding for the RI strains was approximately 2-fold in all regions examined, the core, the shell of the nucleus accumbens (NAc) and the dorsomedial caudate-putamen (CPu); heritability in all regions was moderate--(h2 approximately 0.35). Drd2 expression in forebrain samples from the RI and parental strains ranged 1.5- to h2-fold and was moderate-0.47. Variation in the number of tyrosine hydroxylase (TH) positive neurons was moderate, 41% and 26% and h2 was low--0.19 and 0.15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 49 publications
2
19
1
Order By: Relevance
“…Despite enhancing the sensitivity of our measure by testing after two CS+ (ethanol) exposures, we found that dopamine D2-like receptor blockade did not reduce ethanol-induced CPP acquisition. Although these findings agree with studies showing that dopamine D2-like receptors play only a minor role in ethanol reward (e.g., Cunningham et al 1992; Risinger et al 1992), they oppose others that have shown reduced ethanol-induced CPP in D2 receptor-deficient mice (Cunningham et al 2000) and a robust positive correlation between expression of the dopamine D2 receptor gene (Drd2) and ethanol-induced CPP magnitude (Hitzemann et al 2003). …”
Section: Discussionsupporting
confidence: 86%
“…Despite enhancing the sensitivity of our measure by testing after two CS+ (ethanol) exposures, we found that dopamine D2-like receptor blockade did not reduce ethanol-induced CPP acquisition. Although these findings agree with studies showing that dopamine D2-like receptors play only a minor role in ethanol reward (e.g., Cunningham et al 1992; Risinger et al 1992), they oppose others that have shown reduced ethanol-induced CPP in D2 receptor-deficient mice (Cunningham et al 2000) and a robust positive correlation between expression of the dopamine D2 receptor gene (Drd2) and ethanol-induced CPP magnitude (Hitzemann et al 2003). …”
Section: Discussionsupporting
confidence: 86%
“…For example, the wide variation among individuals in striatal Drd2 expression seen in this study and elsewhere (e.g. Hitzemann et al 2003) is not correlated with the expression of “epigenetic” related genes but has marked behavioral consequences ( Hitzemann et al 1995). Understanding the causes of such variation will be key to developing new therapeutic strategies for the treatment of alcoholism and other drugs of abuse.…”
Section: Discussioncontrasting
confidence: 48%
“…For example, synaptic trafficking/scaffolding molecules including Syntaxin 12 (Weng, Symons, & Singh, 2009) and Munc18-1 (Fehr et al, 2005) help control ethanol consumption/preference. Additionally, dopamine D2 receptors appear to regulate ethanol reward, as represented by conditioned place preference (Hitzemann et al, 2003). Notably, dependence-enhanced ethanol drinking has not been as extensively studied using recombinant inbred lines.…”
Section: Introductionmentioning
confidence: 99%